Remote Patient Monitoring with Predictive Alerts: Advancing Proactive Healthcare through Integrated Technology - Vudathala, Nageswara Rao (International Journal of Computing and Engineering, 2025)
Distance patient monitoring (RPM) represents a transformational advancement in healthcare distribution with future alert, enabling active intervention through continuous physical monitoring and sophisticated data analytics. This scholarly article examines the emergence and implementation of the RPM system in contemporary healthcare settings, discovering its technical architecture, clinical applications, implementation challenges, and future directions. The integration of wearable sensors, safe communication infrastructure, and machine learning algorithms creates unprecedented opportunities for personal health management beyond the traditional clinical environment. These systems display adequate benefits in heart, diabetes, respiratory, and post-operative care domains, with hospitalization, emergency department throughput, and cuts in mortality. Progress from reactive to advanced care models through RPM technologies marks a paradigm change in clinical practice, providing special benefits for the aging population and people with limited healthcare access. Trained machine learning models on multimodal physiological data can detect subtle deviations from individual baselines, providing important initial warning indications before traditional monitoring approaches can identify abnormalities. Despite hypnotizing evidence supporting their efficacy, significant implementation obstacles persist, including technical limitations, workflow integration complications, workforce preparation interval and oral issues. The future trajectory of RPM will be shaped by integration with continuous technological progress in flexible bioelectronics, algorithm innovations, and complementary reality interfaces and supplementary technologies such as Federated Learning. When the extensive care model is posted in a thoughtful way, these technologies have the ability to fundamentally redefine the boundaries of effective health care distribution.